PERAN SENI MUSIK DALAM PERKEMBANGAN ANAK-ANAK TUNA NETRA DI SEKOLAH DASAR - Nisa, Mar'atun; Karwiani; Purnama S, Intan; Sulastri; Nabila, Putri; Hasanah, Niswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to conduct a systematic review of the literature regarding the role of musical arts in the development of blind children in elementary schools. The type of research used is a Systematic Literature Review approach with a qualitative approach. A total of 39 relevant articles were found through Scopus, DOAJ and Google Scholar indexing, selected based on the year 2013-2023. The research results show that the art of music has great potential to provide significant benefits for the sensory, cognitive, social and emotional development of blind children. Music has been proven to be able to stimulate sensory development, especially in terms of hearing, kinesthetics and touch, which are important aspects for individuals with visual impairments. Additionally, participation in musical activities can also improve spatial cognition and overall cognitive abilities, as well as provide important social and emotional benefits, such as increased social interaction, self-confidence, and inclusion in the community. Adapted music learning approaches, including the application of Universal Design for Learning (UDL) principles and the use of active music methods, have proven effective in supporting the learning and development of blind children in elementary schools. Keywords: blind children, elementary school, music arts